Poland as a Priority Country for the Education Migration of Young Ukrainians - Cherusheva Н. B.; Parkhomenko, V. V. (Statistics of Ukraine, 2021)
Intensification of the integration processes in education helps increase the quality of the international education and enhance the striving of youth to receive education services abroad. The economic cooperation of Ukraine with EU countries is gradually taking shape, resulting in the rapidly growing demand of Ukrainian students for education in European higher education establishments (HEEs). The European education system is a global leader in training highly skilled staff due to the implementation of dual training which founder was German. The practice of combined training and internship has spread across Europe and gained extreme popularity in Polish HEEs, thus laying grounds for the increasing demand for their graduates. In focus of the article is the international education migration of young Ukrainians, first and foremost to Poland, with highlighting the advantages of training in this country that has been recognized as the most optimal one on the European area with respect to professional training. This is due to several reasons: first, the overwhelming majority of Ukrainian graduates from Polish HEEs showed professional competencies and mental fitness for work in companies and enterprises across EU; second, Poland is one of the most attractive foreign partners and investors of Ukraine, which promotes rapid development of collaborative Ukrainian-Polish projects. Poland has been working hard in the latest years to develop and improve the system of education services for foreigners, beginning with language courses for training of professionals with various qualification levels and scientific degrees. The received education services, apart from being an effective means for professional and individual development, can help in the carrier promotion at companies in Poland and beyond. The study covers a social-psychological and economic-statistical analysis of the education migration of Ukraine in the latest years, with determining a range of factors that caused one’s choice of other country for getting education services, and investigating the consequences of Ukrainians’ travels abroad for education purposes.